Managing 3-mono-chloropropane-1, 2-diol (3-MCPD) esters during palm oil refining - Zulkurnain, Musfirah (2012)
Contamination with 3-monochloropropane-1,2-diol esters (3-MCPD) in a palm oil physical refining process was studied, and their analytical, chemical and processing factors were determined for mitigation purposes. For monitoring purposes, two disputable indirect methods, acid transesterification and alkaline transesterification method were compared, and the best method for the determination of 3-MCPD esters in oil samples using gas chromatography-tandem mass spectrometry (GC-MS/MS) was validated in-house. The acid transesterification method showed better analytical relevance over the alkaline transesterification method, with a method detection limit (MDL) of 0.006 mg/kg, a method quantification limit (MQL) of 0.019 mg/kg and excellent recovery (93-105%) and precision (%RSD) (1.3-4.2%). Palm oil was found to contain the highest levels of 3-MCPD esters (2.36 ± 0.12 mg/kg) compared with other types of refined vegetable oil. The quantification of industrial palm oil samples at different stages of the refining process confirmed major formation of 3-MCPD esters during the deodorization stage and the formation of a small amount (11.2%) during the pre-treatment stage. Subsequently, factors that contribute to formation of 3-MCPD esters in the palm oil refining process were assessed, including the effect of different crude palm oil (CPO) quality and refining parameters at all stages of the refining process. Poor quality CPO with a high phosphorus content (8.8 ppm) and a low deterioration of bleachability index (DOBI) value (2.4) gave a remarkably high formation of 3-MCPD esters. Utilizing D-optimal design, the effects of the degumming methods (water degumming and acid degumming) and different bleaching adsorbents (n=4) were studied relative to the minor components of palm oil that are likely to be the precursors of the 3-MCPD esters. Water degumming and bleaching with synthetic magnesium silicate significantly (p<0.05) reduced the level of 3-MCPD esters compared with other bleaching adsorbents, possibly due to the removal of precursors of 3-MCPD ester prior to deodorization step. Only phosphorus content exhibited a significant correlation (p<0.05) with the level of 3-MCPD ester (R2=0.686),suggesting that phospholipids might be one of the precursor. The formation of 3-MCPD esters in the refining process also showed dependence on the temperature ofthe deodorization step. The physical refining process was modified with the incorporation of a water degumming and washing step in addition to acid degumming. The synergistic effects of the combination of the adsorbents magnesium silicate and activated clay were utilized for the bleaching step. The modified process was then optimized using response surface methodology (RSM), with five processing parameters: water dosage (0-5%), acid degumming dosage (0-1%), degumming temperature (40-80 °C), bleaching earth dosage (0-1%) and deodorization temperature (220-280 °C), to obtain the greatest reduction in the formation of 3-MCPD esters with an acceptable final refined bleached and deodorized (RBD) palm oil quality. Large reduction in 3-MCPD ester formation was observed with increasing water degumming percentage above 3%, reducing degumming temperature and increasing bleaching clay dosage. The color removal was significantly (p<0.05) influenced by increasing in all of the processing factors except bleaching clay dosage. The oil stability index (OSI) was significantly (p<0.05) contributed by increasing in acid dosage and degumming temperature, and decreasing in clay dosage and deodorization temperature. Incorporation of water degumming not affected the OSI value. The optimized conditions were 3.5% water dosage, 0.1% acid dosage, a degumming temperature of 60 °C, 0.3% bleaching earth dosage and a deodorization temperature of 260 °C. These conditions resulted in 87.2% reduction in 3-MCPD esters, from 2.948 mg/kg in RBD palm oil refined conventionally to 0.374 mg/kg, with color and OSI values of 2.4 R and 14.3 hrs, respectively. Model verification using one sample t-test at p<0.05 demonstrated the suitability of the established models in explaining the responses as function of the processing parameters.